Pembelajaran Science, Technology, Engineering, Art, and Mathematics (STEAM) Bagi Anak melalui Bermain Bersama Orang Tua - Sriati Sriati; Ivana Kusuma Parahita; Sri Lestari (Warta LPM, 2022)
STEAM (Science, Technology, Engineering, Art, and Mathematics) learning is a method that integrates science, technology, engineering, art, and mathematics in learning so that it can be easily understood by students. STEAM learning is carried out from an early age to help achieve 21st century skills and the industrial revolution 4.0. Parents need to understand STEAM learning in order to be able to assist children in STEAM learning activities through playing activities at home. However, many parents are not familiar with STEAM learning. The purpose of this community service is to help parents prepare to accompany their children to learn STEAM. This community service involved 77 parents and children from TK A & B PAS Assakiinah. This activity begins with collecting initial data on the STEAM learning experience. The implementation stage is carried out by socializing and distributing STEAM learning mentoring modules for parents, STEAM learning practices through playing activities with children and family members at home which are recorded with video, sharing experiences of STEAM learning practices among participants, and evaluating activities. After participating in this community service activity, parents who were previously unfamiliar with STEAM learning became aware of STEAM learning. Parents feel happy when they practice STEAM learning with their children using the modules provided. The reaction of children who are happy and excited when participating in STEAM learning through play makes parents feel comfortable in enjoying togetherness with their children. If this practice continues, it can help build closeness between parents and children in the family. Thus, the STEAM learning module can be used as a guide for parents to assist children in playing activities with their families.